LATE ONSET PSYCHOSIS – A CASE REPORT - Siddiqui, Javed Ather; Qureshi, Shazia Farheen; Metwally, Hamed Hasan; Eldaous, Ali Mahmoud (Journal of Psychiatry Psychology and Behavioral Research, 2024)
Introduction – Late-onset psychosis is a disorder that is well-known but poorly understood, and it has emerged as an increasingly significant issue in geriatric patients. There is no clear information about whether this psychosis occurs for the first time at this age. Despite being underdiagnosed, this late-onset psychosis responds well to treatment. A bizarre, persecutory delusion is a hallmark symptom of late-onset schizophrenia. Methods – Presented the case of a 67-year-old woman who visited the Emergency Psychiatry Department complaining of persecutory thoughts, auditory hallucinations, and mild cognitive impairment. Results – This case report explores the diagnostic process and treatment options for very late-onset schizophrenia-like psychosis, including non-pharmacological and pharmacological approaches. Discuss – Psychotic symptoms can be caused by a variety of general medical conditions in elderly patients. It is necessary to rule out delirium, dementia, substance-related disorders, delusional disorder, and dissociative disorder before diagnosing Late-onset psychosis. A late-onset psychosis is not only challenging to diagnose but also to treat. Non-pharmacological treatments are the first option in managing late-life psychosis. It includes psycho-education for patients and their families, as well as cognitive behavior therapy (CBT). It is important to monitor for adverse reactions while administering medication, and the lowest dosage should be used to achieve short-term efficacy. In addition to antipsychotic medication, anticholinesterase inhibitors may also be effective in treating these patients. Conclusion: A careful observation and approach are required to make an etiological diagnosis of late-onset psychosis since there are no pathognomonic signs or symptoms. To achieve the best results, their efficacy and side effects should be monitored with regularity.  Keywords: late-onset psychosis, dementia, schizophrenia.